Sistem Pakar Diagnosis Penyakit Typhus Menggunakan Metode Forward Chaining Berbasis Web - Abdul Hakim Jambak; Samsir; Shabrina Rasyid Munthe (CSRID (Computer Science Research and Its Development Journal), 2026)
Typhoid fever is a digestive system infection caused by Salmonella Typhi and remains a significant health problem in Indonesia due to symptom similarities with other diseases, which often lead to delayed early diagnosis. This study aims to develop a web-based expert system to support early diagnosis of typhoid fever using the Forward Chaining method. The knowledge base was constructed through medical literature review and expert validation by an internal medicine specialist and represented using IF–THEN production rules. The system utilizes six main symptoms and seven disease conditions processed through a forward chaining inference mechanism to generate diagnostic conclusions automatically. System evaluation was conducted using 146 case datasets through Black Box Testing, White Box Testing, and Known Case Testing. The results show a diagnostic accuracy of 87.88%, while white box testing achieved 100% logical correctness. The findings indicate that the Forward Chaining method effectively performs symptom-based reasoning and can support structured early diagnosis of typhoid fever.